Financial control in the Eurasian Economic Union - Kamenkov, Victor S. (Journal of the Belarusian State University. Law, 2019)
The article analyzes the issues of formation, state and improvement, problems of coordination and coordination of actions in the organization of financial control, requiring the attention of each of the states of the Eurasian Economic Union, affecting the rights and legitimate interests of a large number of persons. In particular, the absence of the definition of «financial control» in the current national legislation of the EAEU countries is emphasized, its approximate definition is formulated. Judicial practice in respect of acts of financial control bodies, as well as judgments on new forms and types of financial control are studied. It is proposed to continue further research, improvement of legal regulation at the national and international levels, its harmonization and even unification, convergence of judicial practice.